FORMULATION AND EVALUATION OF COPPER NANOPARTICLES LOADED MICROSPONGES (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Microsponges become imperative in the field of targeted drug delivery and in other biomedical applications. There was a clamant need for designing microsponges incorporating with green synthesised metal nanoparticles rather than the chemical drug in order to reduce the side effects of the drug and thus increasing the effectiveness of nature of the whole material. It provokes us to design this novel approach of loading copper nanoparticles into the microsponges. Here in this work, microsponges based on ethyl cellulose and polyvinyl alcohol were synthesised by Quasi-Emulsion Solvent diffusion method in which copper nanoparticles procured from Hibiscus rosa-sinensis leaf extract was incorporated. The Loaded microsponges were characterised by High Resolution Scanning Electron Microscopy (HR-SEM) and Particle size distribution Analyzer (PSA). The Drug content and Entrapment Efficiency of the microsponges were found out. The antimicrobial and antioxidant activity of the loaded microsponges were evaluated.